SETTING THE ANALYSIS OF NATURAL RESOURCE USE IN CONTINENTAL AREAS OF INDONESIA BY APPLICABILITY CONVENTION LAW OF PBB 1982 - Abdul Munsharif (UNISSULA, 2018)
Before the entry into force of UNCLOS in 1982, the continental shelf area governed by Article 1 of the Convention IV Geneva Convention on the Law of the Sea in 1958, which was implemented a by Act No. 1 of 1973. The setting through 1958 Geneva Convention on the Law of the Sea benefit only for the developed countries that have the advanced technology. Although UNCLOS 1982 has been in force, but the status of Indonesian Act No. 1 of 1973 still impose as the implementation of the Geneva Conventions Of 1958. Several agreements with neighboring countries are being held between the years 1969- 19972, of course it is very detrimental to the Indonesian Government. In this case the Act No. 1 of 1973, adjusted to international law, namely UNCLOS in 1982 is expected that the regulating of the utilization of natural resources in the continental shelf of Republic Indonesia can provide a fair arrangement. It is Necessary to remember that there is a difference in perception between the Act No. 1 of 1973 with the UNCLOS in 1982 in the matter of setting the area of the continental shelf.